The FT-IR, FT-Raman, 1H and 13C NMR study on molecular structure of sodium(I), calcium(II), lanthanum(III) and thorium(IV) cinnamates. Issue 3 (2010) - Kalinowska, M.; Lewandowski, W.; Swislocka, R.; Regulska, E.
Abstract : In this work the effect of sodium(I), calcium(II), lanthanum(III) and thorium(IV) ions on the electronic structure of cinnamic acid (phenylacrylic acid) was studied. In this research: infrared (FT-IR), Raman (FT-Raman), nuclear magnetic resonance ( 1 H, 13 C NMR) were used. In the series of Na(I)→ Ca(II)→ La(III)→ Th(IV) cinnamates: (1) systematic shifts of several bands in the FT-IR and FT-Raman spectra, and (2) regular chemical shifts of protons 1 H and 13 C nuclei were observed.